FERRIC SULFATE DAPAT MENYEBABKAN PEWARNAAN INTERNAL DENTIN - Nurlitasari, Dewi Farida (Faculty of Dentistry, Mahasaraswati Denpasar University, 2018)
Tooth discoloration is a problem that can interfere the aesthetic. Tooth discoloration can be caused of extrinsic, intrinsic or internal. One of the causes of internal dentin discoloration is due to gingival retraction. The purpose of this study is to discuss discoloration on the dentin that can be caused by chemicals fluid in retraction cord. In fixed restorations procedure, gingival retraction is necessary to obtain an accurate cervical impression. One of the causes of internal dentin discoloration is due to gingival retraction by mechanochemical that uses a combination of gingival retaction fluid (GRF) contain ferric sulfate and knitted retraction cord. Conclusion, internal dentin discoloration caused of gingival retraction used material contain ferric sulfate can be seen under porcelain restoration.